2020
DOI: 10.1093/nop/npaa063
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation practices for children with diffuse intrinsic pontine glioma

Abstract: Background Diffuse intrinsic pontine gliomas (DIPGs) are a leading cause of brain tumor deaths in children. Current standard of care includes focal radiation therapy (RT). Despite clinical improvement in most patients, the effect is temporary and median survival is less than one year. The use and benefit of reirradiation has been reported in progressive DIPG, yet standardized approaches are lacking. We conducted a survey to assess reirradiation practices for DIPG in North America. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Various fractionation regimens have been utilized, but CF of 1.8-2 Gy has predominated. 9 In initial treatment of DIPG, there does not appear to be a role for hyperfractionation. 25 However, interest in HF has emerged, given the value of decreased patient and caregiver burden with fewer treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various fractionation regimens have been utilized, but CF of 1.8-2 Gy has predominated. 9 In initial treatment of DIPG, there does not appear to be a role for hyperfractionation. 25 However, interest in HF has emerged, given the value of decreased patient and caregiver burden with fewer treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In a published survey, 30% of responding physicians reported symptomatic radiation necrosis and 43% reported asymptomatic radiation necrosis as complications of reRT in this setting. 9 In published series, this toxicity has been rare, but it remains an important risk to consider for dose escalation or HF, as consequences can be severe. In the dose escalation series in India, two patients who received 43.2 and 45 Gy developed sudden onset headache and neurologic dysfunction, and they were found to have intratumoral hemorrhage 7 and 77 days after reRT, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies confirmed a statistically significant median survival benefit after re-irradiation for recurrent DIPG, ranging from 3 to 4 months. The maximum doses reported in the literature ranged from 30 to 36 Gy (1.8 Gy/day), according to the time passed since their first radiation therapy to permit some recovery of brainstem tolerance [ 57 ].…”
Section: Current Treatmentsmentioning
confidence: 99%
“…Nonetheless, despite the various attempts at new treatment approaches described so far, the prognosis remains poor (8). Re-irradiation, which represents the only effective treatment for recurrent disease, can lead to symptom relief or neurological improvement in the majority of patients and slightly prolong survival after relapse but remains a palliative and not a curative option (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%